The Role of Peer Counseling Services in Addressing Juvenile Delinquency among High School Students - Yunita Yunita; Paulinus Alexander Satriano Uda (International Journal of Counseling and Psychotherapy, 2025)
Background: Student delinquency is a persistent issue that affects the learning environment and overall student development. It can disrupt academic progress, harm peer relationships, and contribute to long-term behavioral problems. Objective: This study aims to investigate the influence of peer counseling on student delinquency. Specifically, it seeks to determine whether peer-based interventions can serve as an effective strategy for reducing delinquent behavior among high school students. Method: A correlational research design was employed at SMA Kartika I-2 Medan in 2022, with a sample of 40 students. Data were collected using structured questionnaires and analyzed through statistical methods to examine the relationship between peer counseling and student delinquency. Result: The results revealed that peer counseling does not have a significant impact on reducing student delinquency. Instead, other influential factors were identified, including the family environment, school climate, personal motivation, and broader social conditions. Conclusion: The study concludes that peer counseling alone is insufficient as an intervention for addressing student delinquency. More comprehensive strategies are required to tackle the root causes of delinquent behavior. Contribution: The findings contribute to the field of educational psychology and counseling by emphasizing the importance of multi-faceted intervention approaches.